The Cost of Youth Voices: Comparing the Feasibility of Youth GO Against Focus Groups - Sara T. Stacy; K. Malulani Castro; Ignacio D. Acevedo-Polakovich (Journal of Participatory Research Methods)
Despite the value and impact of meaningfully engaging youth within evaluation and research, many barriers to their engagement within community-based projects exist. In light of these barriers, Youth Generate and Organize (Youth GO) is a participatory approach for integrating youth in research and evaluation that responds to the practical limitations and constraints within community contexts. In this study, we examine the feasibility and saliency of Youth GO, by comparing this approach against traditional focus groups, an established and engaging qualitative method. To compare these two approaches, we implemented a field-based double-blind active comparison trial whereby facilitators and youth were assigned to participate in one of two conditions—Youth GO or a focus group. We examined both conditions on implementation fidelity, implementation cost, and self-reported perceptions from adult facilitators and youth perspectives. Results indicate that when compared to focus groups, Youth GO represents an equally effective—albeit more cost and time efficient—participatory qualitative method for researchers and practitioners that desire to collaborate with youth. Insights from the current study aim to foster the advancement of methods that engage youth in research and evaluation yet respond to the needs and resources present within community settings.